Local Administration of Insulin-like Growth Factor I into Silicon Rubber Chamber Improves Peripheral Nerve Repair in Rats - Rahim Mohammadi; Masoume Masoumi-Verki; Sima Ahsan; Keyvan Amini (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Introduction: Organ reinnervation and functional recovery following peripheral nerve injury still remains a major challenge and return of functional recovery to the preinjured level rarely occurs.The aim was to evaluate the effect of locally administered insulin-like growth factor (IGF I) on nerve regeneration. Methods: Eighty male white Wistar rats were divided into four groups (n = 20), randomly: Intransected group (TC), left sciatic nerve was transected and stumps were fixed in the adjacent muscle.In treatment group defect was bridged using a silicone conduit (SIL/IGF) and filled with 10 μL IGF I (100 ng/kg). In silicone graft group (SIL), the graft was filled with phosphate-buffered saline alone. In shamoperated group (SHAM), sciatic nerve was exposed and manipulated. Each group was subdivided into three subgroups of five animals each and studied 4, 8 and 12 weeks after surgery. Results: Behavioral testing, sciatic nerve functional study, gastrocnemius muscle mass and morphometric indices confirmed faster recovery of regenerated axons in SIL/IGF than in SIL group (p< 0.05). In immunohistochemistry, location of reactions to S-100 in SIL/IGF was clearly more positive than that in SIL group. Conclusion: When loaded in a silicone graft, IGF I accelerated and improved functional recovery and morphometric indices of sciatic nerve. Thus, dose-response studies should be conducted for IGF I to determine the combination of the graft and the compound that achieve maximal efficacy in nerve transection models.